The mechanism of action of the negative Regulators of jak/stat singnaling pathway in Resistant FLT-ITD acute myeloid leukaemia cells - Johan, Muhammad Farid (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2019)
The aim of this study was to understand the mechanism of action of negative regulators of JAK/STAT signalling pathway in FLT3-ITD AML cell lines with different response towards the FLT3 inhibitors PKC412 and CEP701. The cytotoxic dose of CEP-701 and PKC-412 on resistant cell lines was significantly higher in comparison with parental and MV4-11 R-cep+5-Aza (p=0.004) and MV4-11pkc+5-Aza (p=0.003). The resistant cells showed a significant higher viability and lower apoptosis compared with others (p<0.001 ). Expression of SHP-1 and PRG2 were 7 and 20- folds higher in MV4-11R-cep+5-Aza compared to parental and resistant (p=0.011). There was significant hypomethylation (p=0.002) in CpG islands of SHP-1 and PRG2, associated with their re-expressions. The higher sensitivity to TKI was associated with STAT3 inactivation in 5-Aza treated compared with their resistant cell lines. 20-PAGE showed the number of protein spots detected were 522±29 with 79% matching rate which resulted in three upregulated proteins. The restoration of SHP-1 and PRG2 expression induces sensitivity towards CEP-701. 5-Aza enhances efficacy of TKI and treatment with 5-Aza followed by PKC-412 or CEP-701 could provide suitable candidates for further investigates to underline alternative options for the treatment of AML patients with FL T3-ITD.